2014
DOI: 10.1016/j.molonc.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 1 modulates invasion and metastatic potential of colorectal cancer cells

Abstract: Suppressor of cytokine signaling (SOCS) 1 is an inducible negative regulator of cytokine signaling but its role in human cancer is not completely established. Here we report that, while SOCS1 is expressed in normal colonic epithelium and colon adenocarcinomas, its level decreases during progression of colon adenocarcinomas, the lowest level being found in the most aggressive stage and least differentiated carcinomas. Forced expression of SOCS1 in metastatic colorectal SW620 cells reverses many characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
2
24
2
Order By: Relevance
“…29 Overexpression of SOCS1 increased the mir-200 family of miRNAs, which promotes the mesenchymal-epithelial transition and reduces tumor migration in colon cancer cells. 30 These studies demonstrated the crucial role of sfrp1, dkk3, Figure 3. FFAR2 deficiency changed histone modification on inflammation regulators.…”
Section: Discussionmentioning
confidence: 85%
“…29 Overexpression of SOCS1 increased the mir-200 family of miRNAs, which promotes the mesenchymal-epithelial transition and reduces tumor migration in colon cancer cells. 30 These studies demonstrated the crucial role of sfrp1, dkk3, Figure 3. FFAR2 deficiency changed histone modification on inflammation regulators.…”
Section: Discussionmentioning
confidence: 85%
“…Their findings are somewhat contradictory. In the David et al study, the highest SOCS1 mRNA and protein levels were seen in normal colon and early-stage adenomas, whereas the lowest levels were detected in advanced and poorly differentiated carcinomas 22 . Nonetheless, high SOCS1 protein level was still noted in 63% of advanced stage IV CRC tumours.…”
mentioning
confidence: 85%
“…Notably, CIMP colorectal tumours are associated with specific genetic features and poor clinical outcomes 20 21 , but SOCS1 methylation in CIMP CRCs has been linked to better overall patient survival than those without 18 . Only two recently published studies have so far probed the abundance of SOCS1 mRNA or protein in relatively small cohorts of human CRC samples 22 23 . Their findings are somewhat contradictory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What's more, SOCS1 and JAK2/STAT3 pathway are discussed in hepatocellular carcinoma [24]. David et al uncover that the overexpression of SOCS1 give rises to cell morphology changes and obviously reduced tumor cell invasion in vitro [25]. In this study, the results of recuse assays demonstrates that JAK2/STAT3 signaling pathway inactivation caused by GATA6-AS1 overexpression, is reversed by silencing of SOCS1 and Colivelin.…”
Section: Discussionmentioning
confidence: 52%